The Evaluatıon Of Some Reference Planes Used In Cephalometrıc Researches: A Methodologıc Study (Galenos Yayinevi, 1989)
Reference planes are frequently used in cephalometric researches in order to obtain more reliable results. For this purpose, different reference planes are used. Does the utilization of different reference planes make no difference in the results obtained or do they affect them? The aim of this study is to find an answer to this question. By establishing two different reference planes on the same tracings; the distances of certain anatomic points to these planes are measured on the pre-post treatment and control films. Then, the pre-post means of these measurements are evaluated by t-test. As a result, it is found out that the means and the results of t-test may give different conclusions at the same points on different planes.